2001
DOI: 10.1116/1.1410948
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of thin lead oxide films produced by reactive direct current magnetron sputtering

Abstract: The structural and optical properties of thin lead oxide films were studied. Thin films were prepared by reactive dc magnetron sputtering of lead (Pb) targets in an Ar/O2 mixture. The structure has been determined by x-ray diffraction measurements, which show that crystalline lead oxide films of different composition (PbO, PbO1.44, Pb2O3, and PbO2) have been formed upon increasing oxygen flow (partial pressure). This result is confirmed by Raman spectroscopy. The effect of postdeposition annealing on the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 28 publications
6
41
0
Order By: Relevance
“…E g values of 1.9 and 2.5 eV were found for the tetragonal and orthorhombic structure of PbO, respectively [28]. For Pb 3 O 4 an experimental value of 2.1 to 2.2 eV is reported, while for PbO 2 a value of 4.2 has been measured for α-PbO 2 phase and a value of 1.5 eV has been reported for β -PbO 2 [29,30]. The band gap values obtained in this work are consistent with the values reported in the literature [28].…”
Section: Optical Propertiesmentioning
confidence: 84%
See 1 more Smart Citation
“…E g values of 1.9 and 2.5 eV were found for the tetragonal and orthorhombic structure of PbO, respectively [28]. For Pb 3 O 4 an experimental value of 2.1 to 2.2 eV is reported, while for PbO 2 a value of 4.2 has been measured for α-PbO 2 phase and a value of 1.5 eV has been reported for β -PbO 2 [29,30]. The band gap values obtained in this work are consistent with the values reported in the literature [28].…”
Section: Optical Propertiesmentioning
confidence: 84%
“…Lead oxide thin films have been laid on by both physical and chemical deposition methods. Physical methods reported in the literature include pulsed laser-assisted deposition [17], dc and rf magnetron sputtering [18], while chemical methods include spray pyrolysis [13,14] and electro deposition [19]. Amongst the chemical methods used to fabricate lead oxide thin film, spray pyrolysis method is simple, inexpensive, and capable of producing films on large scale area for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…For crystalline materials, interstitial defects induce a large lattice distortion into their immediate neighbourhood that results in their high formation energy [15]. In this regard, the crystal lattice of polycrystalline α-PbO is unique, because the distance between weakly interacting layers is large enough to accommodate a foreign atom (c 0 = 5.07Å [14]). Therefore, along with the vacancy defects, formation of the interstitials is expected to be inherent to the α-PbO lattice.…”
Section: Crystallographic Defects In α-Pbomentioning
confidence: 99%
“…Because the size of the band gap is crucial in order to correctly define the appearance of the defect states inside the band gap, the band structure properties have been evaluated for the optimized lattice parameters. However, for calculations of the defect formation energy, an adjustment of the interlayer distance by using the experimental data of the lattice constant (c 0 = 5.07Å [14]) has been performed. It was found that only the formation energy of the Pb interstitial is considerably affected by the mismatch in the lattice parameters, caused by the poor incorporation of Pb atom of large atomic radius between the layers (the formation energies of the vacancy defects have been pointed out not to be affected by GGA limitation in our previous work [5]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation